Early marriage practices and the health impacts on female adolescent health in Central Lombok: a qualitative study - Baiq Rizka Herliana; Ni Wayan Arya Utami; Desak Putu Yuli Kurniati (Universitas Udayana, 2018)
Background and purpose: Early marriage through merariq or eloping tradition is a common practice in West Nusa Tenggara particularly in Central Lombok. Early marriage leads to several negative consequences on the reproductive health of female adolescents. This study aims to explore early marriage practices and its impacts on the reproductive health of female adolescents in Central Lombok. Methods: A qualitative study with a case study approach was conducted, and seven early married female adolescents purposively selected as the study participants. Interviews were also conducted with two family members of the female adolescents, one community leader, and a midwife who worked as an adolescent health coordinator at a public health centre. Data were analyzed using a thematic approach to map the reasons for early marriage and its impacts on the reproductive health of female adolescents. Results: Our in-depth interviews revealed that several reasons associated to early marriage practices were: lacking in knowledge regarding the effects of early marriages, perceived benefits of early marriages including perception on maturity and logical thinking, and social sanctions from the society because it considered a disgrace when the eloped girl returned home. Several negative consequences of early marriages emerged from this study were complicated pregnancy/delivery, low birth weight, and undernourished children. Our informants concerned about the psychological effects of early marriages which include fear, regret, and depression. Eloped female adolescents lose their agency for decision making including the right for further education. Conclusions: Early marriage practices bring negative health consequences to female adolescents. An active collaboration across health sector and community leaders is required to provide sufficient information regarding the harmful effects of early marriages. Also, a more effective communication strategy using a family-based approach is required to appropriately target female adolescents with health information associated with the impacts of early marriage.